Pathologic Changes in the Liver During Acute Exposure to Clozapine and Its Combination with Ethanol (Experimental Study) - O. L. Romanova; D. V. Sudukov; M. A. Golubev; M. L. Blagonravov; V. V. Goshkoev; A. A. Churilov (Общая реаниматология)
Purpose: identification of pathological changes in the liver at early stages of the effect of clozapine and clozapine combined with ethanol to improve the diagnosis of this acute exposure.Materials and methods. The experiments were carried out on outbred male rats (n=15). The animals were split into 3 groups, 5 animals in each: 1) control (intact rats); 2) clozapine, 3) clozapine and ethanol. Clozapine at a dose of 150 mg/kg of the animal’s body weight was administered orally under anesthesia (chloralose), clozapine (150 mg/kg) with ethanol at a dose of 5 ml/kg — orally. Rats were removed from the experiment after 3 hours by decapitation. Samples of liver tissue were studied using light microscopy. During histological examination, the following morphological signs were evaluated: blood circulation disorder (presence of venous, capillary, and arterial congestion, appearance of venous hemorrhage), absence of nuclei staining, cytoplasm lumpiness, cytoplasm vacuolation, presence of necrosis foci, appearance of cellular response (a large quantity of leukocytes per power field). The assessment was done using the F-test. Forensic chemical analysis was carried out using a high-performance liquid chromatograph equipped with a mass detector. The content of clozapine, norclozapine, and clozapine-N-oxide in blood serum and liver homogenate of rats was evaluated.Results. In the control group, no pathological changes in liver tissue were observed. 3 hours after clozapine administration, venous congestion was detected. 3 hours after administration of clozapine and ethanol combination, venous congestion and absence hepatocyte nuclei staining were observed. It was found that after combined administration of clozapine and ethanol, the blood serum clozapine was 1.94-fold and clozapine-N-oxide was 2.3-fold lower than when clozapine was administered as a single drug while the content of norclozapine showed no difference.Conclusion. Changes detected in the liver, together with changes in other organs and findings of the forensic chemical analysis, allow establishing the fact of clozapine poisoning. Understanding of the processes going on in the body during such intoxications helps rendering medical assistance to victims more effectively.